Перспективи побудови та розвитку децентралізованої енергетичної системи України на основі мікромереж - Шевчук, О.А.; Черняєв, М.О. (Економічний вісник Донбасу, 2024)
У статті розглядаються технічні, економічні та політичні аспекти впровадження децентралізованої енергетичної системи в Україні на основі мікромереж, з урахуванням сучасних геополітичних викликів. Визначено, що енергетична безпека країни зазнала серйозних загроз через військову агресію, що призвела до значних руйнувань енергетичних об’єктів, підстанцій та розподільчих мереж. Доведено потребу переходу від великих централізованих енергомереж до менших, більш стійких децентралізованих систем. Обґрунтовано впровадження мікромереж, що інтегрують відновлювальні джерела енергії, таких як сонячна, вітрова, біомаса та гідроенергетика та являють собою перспективне рішення для підвищення енергетичної безпеки і зменшення залежності від зовнішніх джерел енергії. Визначено переваги мікромереж, зокрема їх здатність функціонувати автономно під час відключень у центральній системі, зменшувати залежність від викопного палива та сприяти інтеграції відновлюваних джерел енергії. Розглянуто виклики, з якими стикається перехід до децентралізованої енергетики, зокрема високі початкові витрати, застаріла інфраструктура та відсутність чіткої законодавчої бази для регулювання діяльності мікромереж. Обґрунтовано потребу в системних законодавчих реформах для регулювання діяльності мікромереж, стимулювання інвестицій та сприяння децентралізації енергетичної системи. Спираючись на кращі практики таких країн, як Данія та Німеччина, запропоновано рекомендації щодо інтеграції мікромереж в енергетичну систему України. This study investigates the technical, economic, and political aspects of developing a decentralized energy system in Ukraine based on microgrids amid ongoing geopolitical challenges. The critical state of Ukraine's centralized energy system, worsened by military aggression and infrastructure destruction, necessitates a transition to a more resilient and flexible decentralized model. The research emphasizes the role of renewable energy sources such as wind, solar, biomass, and hydropower in creating a sustainable energy system. Microgrids, with their capacity for local energy generation, storage, and distribution, are identified as a promising solution to enhance energy security and independence. The analysis highlights the significant advantages of microgrids, including their ability to operate independently during outages, reduce reliance on fossil fuels, and facilitate the integration of renewable energy. However, the study underscores several challenges, including the high costs of implementing microgrids, outdated infrastructure, and a lack of comprehensive legal frameworks. Addressing these issues requires international investment, government support, and the promotion of modern renewable energy technologies. The findings emphasize the critical need for systemic legislative reforms to regulate microgrid operations, incentivize investments, and promote energy decentralization. Drawing on global best practices, particularly from Denmark and Germany, the study provides recommendations for integrating microgrids into Ukraine’s energy landscape. Key measures include financial incentives for renewable projects, enhancing public-private partnerships, and fostering international collaboration to attract investments and transfer technology. The study concludes that transitioning to a decentralized energy system is vital for Ukraine’s economic and energy security, particularly in wartime. By leveraging renewable energy, implementing microgrid solutions, and modernizing energy infrastructure, Ukraine can build a resilient and sustainable energy future.